Pengaruh Kreativitas pada Pemecahan Masalah Matematika Suatu Kajian Meta-Analisis Terhadap Siswa SMA - Hamda, Hamda (Issues in Mathematics Education (IMED), 2024)
This study aims to investigate the influence of creative thinking on problem-solving abilities in mathematics among high school students through a meta-analysis approach. Creative thinking is considered a crucial skill that can enhance students' ability to tackle mathematical challenges in innovative and effective ways. This meta-analysis synthesizes results from 25 independent studies, with a total sample of 359 high school students meeting the inclusion criteria. The findings of the meta-analysis indicate that creative thinking has a significant positive impact on mathematical problem-solving abilities, with an average effect size (Cohen's d) of 0.75 (95% CI [0.60, 0.90]). The heterogeneity analysis reveals significant variability among the included studies, indicated by Q(24) = 55.84 and I² = 57.1%. Moderator factors such as teaching methods, educational context, and student characteristics were analyzed to further understand the variation in findings. Studies employing project-based learning or problem-based learning methods exhibited higher effect sizes (d = 0.85) compared to conventional teaching methods (d = 0.65). Additionally, students with high motivation levels and those in supportive educational environments demonstrated better outcomes in mathematical problem-solving (d = 0.90 and d = 0.80, respectively). These findings underscore the importance of integrating creativity-promoting approaches in high school mathematics curricula. Approaches such as problem-based learning and project-based learning can serve as effective strategies in enhancing students' creative thinking abilities.. Therefore, the findings of this study are expected to provide guidance for educators and policymakers in designing more effective and innovative teaching strategies.